Penyuluhan Pentingnya Pemahaman Hukum Kewarisan Islam Menurut Kompilasi Hukum Islam bagi Anak-anak Yatim dan Duafa di Panti Asuhan Muhammadiyah Tembilahan - Ridwan, Muannif; Hidayanti, Sri; Syaputra, Didi; Niswah, Muhlishatun; Alfassa, Achmad Isya (Indra Institute Research & Publication, 2024)
This article describes the implementation of lecturer service in providing material on the importance of understanding Islamic Inheritance Law according to the Compilation of Islamic Law for Orphans and Duafa in the Muhammadiyah Tembilahan orphanage. The urgency of this activity is carried out to add insight into the right to inheritance distribution according to the Compilation of Islamic Law. The partner's problem is that there are still many orphans and poor children who do not comprehensively understand their rights in getting a share of the inheritance. Therefore, the purpose of this activity is to provide understanding to them so that later they get their rights in accordance with the applicable rules according to the compilation of Islamic law. The implementation of this activity used lecture and discussion methods. There were 35 participants who participated in this activity. This activity was welcomed enthusiastically by the partners. The indicators of the success of this service activity are evidenced by several children who feel satisfied and happy with this activity. Furthermore, it is recommended to carry out similar activities on an ongoing basis to improve and hone their ability to understand Islamic inheritance law in order to realize a harmonious and blessed life in the world and the hereafter.